2012
DOI: 10.1111/j.1939-1676.2012.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine Multiple Acyl‐CoA Dehydrogenase Deficiency (MADD) Associated with Seasonal Pasture Myopathy in the Midwestern United States

Abstract: Background: Seasonal pasture myopathy (SPM) is a highly fatal form of nonexertional rhabdomyolysis that occurs in pastured horses in the United States during autumn or spring. In Europe, a similar condition, atypical myopathy (AM), is common. Recently, a defect of lipid metabolism, multiple acyl-CoA dehydrogenase deficiency (MADD), has been identified in horses with AM.Objective: To determine if SPM in the United States is caused by MADD. Animals: Six horses diagnosed with SPM based on history, clinical signs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
8
40
0
Order By: Relevance
“…FAD is an important cofactor for fatty acid oxidation and sterol synthesis and is required for activation and oxidation of vitamin B6 (pyridoxine); lipoic acid metabolism (E3 subunit) needed for pyruvate, alpha-ketoglutarate, and branched chain amino acid oxidation; vitamin A activation; 5-methyltetrahydrofolic acid synthesis; niacin and NAD synthesis; and glutathione reduction. Functional deficiency of riboflavin can be produced by dietary and environmental factors (21). Severe riboflavin deficiency can present with a plasma acyl-carnitine pattern similar to multiple acyl-CoA dehydrogenase deficiency (MADD), also known as glutaric aciduria type II (GAII) (22).…”
Section: Control Controlmentioning
confidence: 99%
“…FAD is an important cofactor for fatty acid oxidation and sterol synthesis and is required for activation and oxidation of vitamin B6 (pyridoxine); lipoic acid metabolism (E3 subunit) needed for pyruvate, alpha-ketoglutarate, and branched chain amino acid oxidation; vitamin A activation; 5-methyltetrahydrofolic acid synthesis; niacin and NAD synthesis; and glutathione reduction. Functional deficiency of riboflavin can be produced by dietary and environmental factors (21). Severe riboflavin deficiency can present with a plasma acyl-carnitine pattern similar to multiple acyl-CoA dehydrogenase deficiency (MADD), also known as glutaric aciduria type II (GAII) (22).…”
Section: Control Controlmentioning
confidence: 99%
“…In 2006, a similar condition called seasonal pasture myopathy was recognised in the USA (Finno and others 2006); cases also exhibited a MADD-like biochemical profile (Sponseller and others 2012). Following a botanical survey, it was hypothesised that the condition was caused by ingestion of seeds from Acer negundo (box elder tree) (Fig 5) as these trees were present on all pastures associated with cases.…”
Section: History Of Atypical Myopathy In Europementioning
confidence: 99%
“…It is now believed that SPM is indeed similar to AM as it has been showed that biochemical defects of both syndromes are identical [23, 24]. Cases compatible with a diagnosis of AM also have been reported from Australia [25] and New Zealand (information from AMAG).…”
Section: From the Beginningmentioning
confidence: 99%
“…Horses with AM show hyperglycemia [3, 10, 12, 16, 23, 24] and increased free serum carnitine levels [24], although a decrease in muscle free carnitine has been found [23], whereas humans with MADD have hypoglycemia and decreased free carnitine levels. These differences are possibly explained by species-specific steps in energy metabolism.…”
Section: Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation